Labour market entries and exits of women from different origin countries in the UK - Yassine Khoudja; Lucinda Platt (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
In the context of increasing women's labour force participation (LFP) across Western countries, there remain large differences in LFP for women of different ethnic origins. While existing research has demonstrated that part of these differences can be attributed to compositional differences (age, qualifications, family context etc.) and to differences in gender role attitudes and religiosity, residual 'ethnic effects' typically remain. Further insight into the drivers of such differences has the potential to inform us about factors shaping women's LFP more widely. In this paper we exploit a large-scale longitudinal study of the UK to investigate ethnic differences in both LFP entry and exit probabilities. We examine how far we can account for overall ethnic differences in LFP entry and exit, taking account of individual characteristics, gender role attitudes and religiosity, and the contribution of relevant life-course events. We find that, adjusting for all these factors, Indian and Caribbean women do not differ from White majority women in their labour force entry and exit probabilities but that Pakistani and Bangladeshi women are less likely to enter and more likely to exit the labour market, while Black African women have higher entry rates. We also find that Pakistani and Bangladeshi women's labour market entries and exits are less sensitive to partnership and child-bearing events than other women's.
Keywords: 330; ethnic minority women; labour force participation; labour market transitions; life-course events; gender role attitudes